Soil hydraulic properties under different land use types and soil depth at Arjo-Dhidhessa estate sugar factory, Western Ethiopia - Geleta, Workina; Fufa, Fekadu; Bekele, Abdissa (Frontiers in Soil Science, 2025)
The infiltration process is a significant driver of soil quality and ecological performance that is influenced by several factors, including the soil’s hydraulic characteristics, land use types, and soil depth. This study examines the effects of land use types and soil depth on soil hydraulic properties at the Arjo-Dhidhessa Estate Sugar Factory in Western Ethiopia. Composite soil samples were collected from five distinct land-use types (cropland, irrigated land, forest land, shrubland, and fallow land) at three different soil depths (0–30 cm, 30–60 cm, and 60–90 cm). Field infiltration rates were measured using a double-ring infiltrometer to assess variations in soil hydraulic properties. Results revealed significant variations in soil hydraulic properties among land-use types. Forestland exhibited the highest field capacity (51.46%), available water-holding capacity (21.23%), and soil moisture content (23.74%). In contrast, irrigated land demonstrated the lowest infiltration rates (19.6 cm/hr) and sorptivity (75.3 cm/hr), attributed to soil compaction and nutrient depletion. Hydraulic properties also varied with soil depth, showing diminished water retention and infiltration in deeper layers. These findings highlight the necessity for diversified land management strategies to optimize soil health and water resource sustainability. Integrating forest and shrubland conservation practices can enhance soil organic matter and structural integrity. Additionally, adopting techniques such as conservation tillage and reforestation may mitigate soil degradation and compaction, fostering sustainable agricultural productivity. This study underscores the pivotal role of land use in governing soil hydraulic dynamics. The results advocate for management approaches that prioritize soil health and hydrological efficiency, particularly through the preservation of forest and shrubland ecosystems. By implementing these strategies, policymakers and land managers can support long-term agricultural resilience amid ongoing land-use changes.